Infrastructure Driven DevOps in Regulated Markets: A Case Study of Indonesia’s Financial Sector - Sucipto, Purwo Agus (Indonesian Scientific Publication, 2024)
In regulated industries such as finance and healthcare, organizations must navigate the competing demands of digital innovation and strict compliance requirements. This study investigates how infrastructure localization enables the adoption of DevOps practices in Indonesia’s compliance heavy sectors. Drawing on qualitative case studies of BCA and Bank Jago, the research examines how local cloud infrastructure, regulatory policies, and platform strategies converge to support agile software delivery. The methodology involves comparative analysis using publicly available institutional documents, cloud provider rollouts, and compliance frameworks. The study evaluates DevOps maturity through organizational strategies, toolchains, and infrastructure readiness while mapping them against regulatory standards such as ISO/IEC 27001 and the Personal Data Protection Act. The findings indicate that local cloud infrastructure helps reduce latency and legal risks, thereby supporting secure CI/CD pipelines. BCA illustrates the benefits of using enterprise-level platform engineering with OpenShift, while Bank Jago showcases the flexibility of cloud-native DevOps through rapid CI/CD deployment. Furthermore, the study discusses the balance between innovation and compliance, stressing the role of platform engineering, multi-cloud strategies, and Compliance as Code in minimizing vendor lock-in and regulatory risks. The conclusion underscores Indonesia’s hybrid DevOps strategy as a blueprint for other emerging markets. Integrating infrastructure, policy, and talent development enables institutions to balance agility with governance, promoting scalable and compliant digital transformation in regulated sectors.